A Educação a Distância e a formação de professores na UFSCar : a autoridade, a autonomia e o corpo mediados pelas Tecnologias da Informação e Comunicação - Verdan, Kelly Cristiane da Silva (Universidade Federal de São Carlos, 2012)
This present work aims to investigate the implementation of distance education as a mode of education with to formation in pedagogy at the University Federal of San Carlos, noting the authority and the body present or absent in pedagogical relationships mediated by Information Technology and Communication. Therefore a study was conducted on Culture, Technology and Education to draw a picture about the prevalence of technology in everyday society, then addressing public policies for the implementation of distance learning in Brazil, highlighting how this type of education occurred on UFSCar. After that, through interviews and questionnaires were analyzed issues mentioned above, through the theoretical framework of critical theory.
Keywords: Educação a distância; Magistério; Tecnologia da informação; Autoridade; Corpo; Autonomia; Distance Education; Teaching, Information Technology; Authority; Body; CIENCIAS HUMANAS::EDUCACAO